2005
DOI: 10.2166/wqrj.2005.036
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Hormonally Active Substances by Wild White Sucker (Catostomus commersoni) Exposed to Effluents Discharged to the Wabigoon River

Abstract: A study was initiated in the spring of 2001 to determine if hormonally active chemicals are bioavailable to white sucker (Catostomus commersoni) residing in the Wabigoon River, downstream of the bleached kraft pulp mill and municipal sewage outfall located in Dryden, Ontario. Females collected during spawning migrations in May 2001 at a near-field exposure site exhibited increased condition factor, liver size and fecundity relative to those collected from a reference site. Liver samples within each site were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
13
2
Order By: Relevance
“…7c), an effect that was also documented in previous studies at 40% (v/v) by Kovacs et al [4], cannot be compared to male walleye as vitellogenin examinations were not performed. However, a previous study on the walleye of the Wabigoon River did examine vitellogenin and found no significant vitellogenin induction in near-field samples [25], although river effluent concentrations were estimated to be significantly lower than 60% (v/v) PME (20-40% [v/v] PME) and therefore not directly comparable to our mesocosm study. It would appear from our data that a lack of effect on females and a decrease in male testosterone are the only variables that display consistent results between our wild fish survey and mesocosm exposure.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…7c), an effect that was also documented in previous studies at 40% (v/v) by Kovacs et al [4], cannot be compared to male walleye as vitellogenin examinations were not performed. However, a previous study on the walleye of the Wabigoon River did examine vitellogenin and found no significant vitellogenin induction in near-field samples [25], although river effluent concentrations were estimated to be significantly lower than 60% (v/v) PME (20-40% [v/v] PME) and therefore not directly comparable to our mesocosm study. It would appear from our data that a lack of effect on females and a decrease in male testosterone are the only variables that display consistent results between our wild fish survey and mesocosm exposure.…”
Section: Discussioncontrasting
confidence: 97%
“…The male from the present study had far more primary oocytes in its testes when compared to the two males from 2000. Occurrences of hormonal imbalance in fish are not limited to walleye, and have been seen in other species [25].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations